Volunter Goes To School (Vogetos) : Sarana Kampanye Mitigasi Bencana di Sekolah - Holidi, Holidi; Hidayat, Nurul (Laboratorium Sosiologi FISIP Universitas Jember, 2020)
This article discusses a new social movement carried out by Volunteers in Jember. In this case, the new social movement Volunteer goes to school. Volunteer Nusantara Jember is a disaster and humanitarian organization, making disaster and humanity the basis of its movement. Nusantara volunteers as an alternative solution to non-structural disaster mitigation and support for education and non-structural disaster mitigation, which is still lacking and is only seen from a budget perspective, an obstacle to disaster mitigation, especially in Jember and its surroundings. This article uses a qualitative descriptive participatory method to provide a detailed explanation of how the movement patterns carried out by Nusantara Jember Volunteers, using the theory of new social movements, to analyze data. This study provides an overview of how Jember Nusantara Volunteers have their campaigns in carrying out the process. Jember archipelago volunteers raised activities on education by making children aware of non-structural disaster mitigation. Focuses its movement on Sociopreneurship-based disaster mitigation applied in the work program, namely Volunteer goes To School (VOGETOS).Keywords: New Social Movements, Sociopreneurship, Disaster Mitigation, Volunteer Goes To School Artikel ini membahas tentang gerakan sosial baru yang dilakukan oleh Relawan di Jember. Dalam hal ini, gerakan sosial baru Volunteer goes to school. Relawan Nusantara Jember adalah organisasi Kebencanaan dan kemanusiaan yang menjadikan 2 aspek tersebut, yakni kebencanaan dan kemanusiaan sebagai basis gerakannya. Relawan Nusantara hadir sebagai solusi alternatif permasalahan mitigasi bencana non struktural dan pendukung pendidikan. Mitigasi bencana non struktural yang selama ini masih kurang dan hanya dilihat dari prespektif anggaran, menjadi kendala mitigasi bencana terutama di Jember dan sekitarnya. Artikel ini menggunakan metode kualitatif deskriptif partisipatif, karena bertujuan untuk memberikan penjelasan detail bagaimana pola gerakan yang dilakukan oleh Relawan Nusantara Jember. Penelitian ini menggunakan Teori gerakan sosial baru untuk menganalisa data dan memberikan gambaran tentang bagaimana Relawan Nusantara Jember memiliki gerakan tersendiri dalam melakukan proses kegiatan. Relawan nusantara Jember mengangkat kegiatan tentang pendidikan, dengan membuat kesadaran terhadap anak-anak tentang mitigasi bencana non struktural. Memfokuskan gerakannya pada mitigasi bencana berbasis Sociopreneurship yang diaplikasikan dalam Program kerja yakni Volunter goes To School ( VOGETOS ).Kata Kunci: Gerakan Sosial Baru, Sociopreneurship, Mitigasi Bencana, Volunteer Goes To School